Effect of Stirring Speed on Characteristics of Fe3O4 Nanoparticles Coated with Polyvinyl Alcohol and Glutaldehyde as a Crosslinker - Rahayu, Lale Budi Hutami; Wulandari, Ika Oktavia; Santjojo, Djoko Harry; Sabarudin, Akhmad (Natural B, Journal of Health and Environmental Sciences, 2018)
Research on Fe3O4 nanoparticles is mostly done because of the unique nature of Fe3O4 which has magnetic properties, non-toxic, biocompatible and easily degraded so it is interesting to investigate as a drug delivery system. This nanoparticles were successfully synthesized by coprecipitation method with variations of stirring rate were 180 rpm (sample A), 250 rpm (sample B) and 320 rpm (sample C). FTIR analysis of Fe3O4 nanoparticles, was absorption at ~585 cm-1 for samples A and B showing the presence of Fe-O magnetite bond and absorption at ~623 cm-1 which were not very sharp for maghemite. However the sample B, only absorption at ~623 cm-1 which is sharp for maghemite (Î³-Fe2O3) because of Fe2O3 cubic is not formed. SEM analysis did not show significant morphological differences in velocity variation. From XRD analysis known that the crystal size for samples A and B respectively of 6.4192 nm and 9.5513 nm for sample C could not be calculated because of many iron oxide phases present in it, so it is difficult to find FWHM. ESR analysis of nanoparticle samples shown Fe3O4 properties were ferromagnetic.